Equilibrium Studies of Transition Metal Complexes with Tridentate Ligands Containing N, O, S as Donor Atoms - Kumar Singh, Devendra; Jha, P.K.; Kant Jha, Raman; Mohan Mishra, Prem; K. Jha, Ashok; Kumar Jha, Sherdendu; Pranesh Bharti, Ram (Asian Journal of Chemistry, 2010)
Stability constants of complexes of Mn(II), Co(II), Ni(II) and Cu(II) chelates of 2-hydroxy-3-methoxy benzylidine thiosemicarbazone have been determined by Bjerrum's method of pH metric titration technique as followed by Irving and Rossotti. The stability constants of chelates of bivalent transition metals is in the order:Cu(II) > Ni(II) > Co(II) > Mn(II) From the value of observed K, free energy change of the complexation reaction have been calculated.